Konsep Kebutuhan Badan Kebijakan Internal Kementerian untuk Respon Kebijakan Terhadap Pembentukan BRIN - Willy Wibowo (Badan Strategi Kebijakan Hukum, 2023)
The current Government policy that integrates all Research and Development Agencies in Ministries and Institutions demands that these agencies must be transformed. To be able to answer various strategic issues and anticipate demands that come from the internal and external environment is the basis for an organization to organize and evaluate internally. Proposed organizational arrangements in this case must have a clear basis and contain analysis of the various aspects needed. The purpose of this scientific work is to provide a concept for transforming a research and development Agency into an internal Policy Agency to avoid duplication of duties and functions in existing Research Agencies. This study uses the policy review type method which is focused on reviewing documents. The need for an Internal Policy Agency at the Ministries/Agencies level is currently very urgent because of the diverse and complex fields of work and to produce quality policies and can be measured by the Policy Quality Index. There are several suggestions for Ministries/Institutions that will form an Internal Policy Agency, among others, transformation must be based on evidence-based needs.